Characteristics, Mineralogy and Spectral Properties of Some Typical Vertisols of Vidarbha, Maharashtra, India - S.K. Ray and Rajeev Srivastava, Sujay S. Gaikwad, Jagdish Prasad* (Journal of the Indian Society of Soil Science, 2021)
Soil characteristics, mineralogy and spectral reflectance properties of four typical Vertisols representing Gondia (P1), Nagpur (P2), Yavatmal (P3) and Akola (P4) districts of Maharashtra were studied. These pedons were moderately deep (P2) to deep (P1) and very deep (P3 and P4). The pedons P3 and P4 had colour in the hue 10 YR, whereas P1 and P3 had colour in the hue 2.5 Y and 2.5 YR, respectively. These cracking clay soils had 82-100% smectite in all pedons except in P1 (64-79%) owing to its retention in present climatic condition. The pH of these soils varied from 5.0-7.5 in P1, 6.9-7.1 in P2, 8.3- 8.4 in P3 and 8.5-8.9 in P4 with increase in depth. The pedons of Akola and Yavatmal in particular were characterized by relatively high exchangeable calcium percentage (ECP), exchangeable magnesium percentage (EMP), CaCO3 and narrow Ca/Mg ratio with low hydraulic conductivity in soils of Akola and Gondia (Ap horizon). Soils of Yavatmal, Nagpur and Akola showed low reflectance but rice-growing pedon of Gondia exhibited high reflectance at different wavelengths due to lighter colour and relatively low smectite content. These soils were classified as Chromic Haplusterts (P1 and P3), Leptic Haplusterts (P2) and Sodic Haplusterts (P4). The absence of kaolin material in soils of Yavatmal indicated that parent material (red bole) of the red shrink-swell soil was not exposed to humid climate in the past.